Temperature measurement in microfludic system - Lim, Yu Qian. (2009)
This project presents an experimental investigation on the temperature measurement in microfludic system. The microchannel consists of two inlets (hot inlet, cold inlet) and two outlets. Deionised water and glycerol were tried out in the experiments. Rhodamine B powder were added into the liquid to study the fluorescence intensity with microscope. However, glycerol seemed to be more appropriate for this experiment with higher intensity at room temperature. With the higher intensity, it allows bigger contrast between the hot and cold fluids. In the first part of the project, different heat addition methods were explored to enable heating on the fluid flowing through the hot inlet. The fluid was heated up from the hot inlet with temperature bath, wire resistance heating and thermoelectric module. It was found that thermoelectric is more suitable for this experiment. Thermoelectric module was also used to cool the fluid flowing through the cold inlet. In the second part of the project, is the designing of the microchannel. Different microchannel designs/shapes were required for different heating method and also to enable optimal heating on the fluid flowing through the hot inlet. Thus, six different microchannel designs were fabricated. Each design was modified from the previous one to enhance better heat addition on the fluid. Eventually, the microchannel design 6 is the most viable designs for this experiment. The third part of the project is to study the effect of the fluid when both hot fluid and cold fluids were mixed in the microchannel. Calibration was done to obtain the temperatureintensity relationship. With the calibration completed, the temperature in the microchannel can be found with the intensity. The intensity decreased with increasing temperature. It was found that the average temperature decreased along the microchannel. The temperature increased across the channel when it moved from the lower temperature to the higher temperature.